PEMANFAATAN NAÃVE BAYES UNTUK MERESPON EMOSI DARI KALIMAT BERBAHASA INDONESIA - Syarifah, Aulia; Muslim, Much Aziz (Universitas Negeri Semarang, 2015)
With the development of science and technology that can rapidly help people in solving all the problems and needs of the increasingly numerous and complex. These problems can be solved by several methods in mathematics one method Naïve Bayes. Naïve Bayes is a derivative of the concept of Bayes theorem. Naïve Bayes has advantages such as simple, fast, and high accuracy. Emotions play an important role in human communication in everyday life. However, the application has not been widely used in the emotions of human and computer interaction. In this study will be developed implementation Naïve Bayes and manufacturing applications using Matlab that can recognize the emotions of sentences in Indonesian language